Supply Chain Legitimation through CSR Reporting - Graham Bowrey; Michael Clements (Australasian Accounting, Business and Finance Journal, 2019)
This conceptual paper explores the legitimating process of corporate social responsibility (CSR) reporting in relation to supply chain management. To date, the literature on CSR reporting, in relating to supply chain management, is based on individual segments within supply chains. This paper introduces a framework for the holistic evaluation of the entire supply chain CSR reporting, including the adoption of social audits as a legitimation tool. The theoretical lens of three perspectives of legitimation (structural-functionalist, social-constructionist and hegemonic) are explored as possible approaches to assess the drivers behind organisations in a supply chain reporting on their CSR performance and management. The main finding of this paper is that the development and implementation of the presented framework for evaluating the CSR reporting of the entire supply chain, including social auditing, is a valuable legitimation tool for organisations in a supply chain, and for the industry within which these organisations operate.
Keywords: Accountability; CSR Performance Reporting; legitimation theory; supply chain management; social accounting; social audit